PENINGKATAN MOTIVASI BELAJAR PESERTA DIDIK DENGAN APLIKASI MATLAB SIMULINK DI SMKN 2 SIGLI (Improving Student's Learning Motivation Through Matlab Simulink Application at SMKN 2 Sigli) - Hari Anna Lastya; Hadi Kurniawan; Suci Irawanda (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2022)
The problem that occurs at SMKN 2 Sigli is the learning process that has not used learning media in the form of application software, one of which is Matlab Simulink which can later simplify and increase the motivation of students in the classroom. This study aims to determine whether the introduction of the Matlab Simulink application can increase the learning motivation of students in class XI at SMKN 2 Sigli and to determine the response of students after the introduction of the Matlab Simulink application in class XI at SMK 2 Sigli. This type of research uses an experimental model with a quantitative approach. The population in this study were all students at SMK N 2 Sigli as many as 751 people. The sample in this study is class XI students, totaling 17 people, sampling using purposive sampling method. This research instrument includes observation and questionnaires. The results of observing the activeness of students using the Matlab Simulink application increased according to the criteria for the percentage of 92.85% (highly motivated). The results of the motivation of students as many as 52.54% who chose very well were included in the moderately motivated category and gave a positive response to the use of the Matlab Simulink application for class XI SMK Negeri 2 Sigli.